2020
DOI: 10.1021/acsomega.0c00862
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Boronized Ti6Al4V/HA Composites by Microwave Sintering in Mixed Gases

Abstract: The effect of atmosphere on the fabrication of boronized Ti6Al4V/hydroxyapatite (HA) composites was investigated by microwave sintering of the mixture of Ti6Al4V alloy, HA, and TiB 2 powders at 1050 °C for 30 min in the mixed gases of Ar + N 2 , Ar + CO, and Ar + H 2 , respectively. The presence of N 2 , CO, and H 2 in the atmosphere caused formations of TiN, TiC, and TiH 2 in the composites, respectively, together with evident microstructural changes that determined the mechanical properties (compressive stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In general, vacuum sintering and atmosphere sintering (typically Ar atmosphere) are used to prevent adverse reactions between different components. For example, the sintering of HA/Ti composites is usually carried out in an argon atmosphere to prevent the oxidation of Ti. Moreover, sintering atmosphere has been proved to have a great influence on the properties of the composites. , Obviously, it is essential to evaluate the effect of atmosphere on the sintering process of HA/Ta composites, which has not yet been reported systematically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, vacuum sintering and atmosphere sintering (typically Ar atmosphere) are used to prevent adverse reactions between different components. For example, the sintering of HA/Ti composites is usually carried out in an argon atmosphere to prevent the oxidation of Ti. Moreover, sintering atmosphere has been proved to have a great influence on the properties of the composites. , Obviously, it is essential to evaluate the effect of atmosphere on the sintering process of HA/Ta composites, which has not yet been reported systematically.…”
Section: Introductionmentioning
confidence: 99%
“…12−14 Moreover, sintering atmosphere has been proved to have a great influence on the properties of the composites. 15,16 Obviously, it is essential to evaluate the effect of atmosphere on the sintering process of HA/Ta composites, which has not yet been reported systematically. The present investigation is an attempt to investigate the influences of sintering atmospheres and temperatures on the properties of HA/Ta ceramic composites.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the boronized Ti6Al4V/HA composite could be prepared by microwave sintering at 1050 °C for 30 min under an Ar atmosphere using Ti6Al4V powder of 15-50 μm, TiB 2 powder of 4-8 μm, and needle-like HA with a diameter less than 20 μm and a length less than 100 μm as raw materials. 12,60,72 Its micromorphology is shown in Fig. 7D.…”
Section: Composites Prepared By Microwave Sinteringmentioning
confidence: 99%
“…Many studies have confirmed that microwave heating could achieve better performance than conventional heating in materials synthesis and processing. [12][13][14][15] Microwave energy is characterized by the volumetric thermal effect due to its large wavelength, which allows the energy to be absorbed in a large material volume (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation